2021
DOI: 10.1177/11795468211029244
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue: The Genetics Behind an Emerging Cardiovascular Risk Marker

Abstract: Evidence points epicardial adipose tissue (EAT) as an emerging cardiovascular risk marker. Whether genetic polymorphisms linked with atherosclerosis are associated with higher EAT is still unknown. We aim to assess the role of genetic burden of atherosclerosis and its association to EAT in a cohort of asymptomatic individuals without coronary disease. A total of 996 participants were prospectively enrolled in a single Portuguese center. EAT volume was measured by Cardiac Computed Tomography and participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
(59 reference statements)
1
6
0
1
Order By: Relevance
“…Possible explanations are as follows: rst, the subjects in the study were at different stages of the disease or had different risk factors in addition to the disease; second, previous studies have mostly studied EAT thickness through ultrasound, whereas our study used CMR( as gold standard) to study EAT volume; and third, participants are grouped differently in different studies, which may cause differences in the ndings. Furthermore, the close relationship between BMI and visceral fat has been con rmed, and EAT volume may depend on BMI level [30]. Overall, we highlighted that obesity represented by BMI was the primary risk factor for subclinical left cardiac function impairment in this study, and high EAT levels contribute to risk strati cation for subclinical left cardiac dysfunction.…”
Section: Discussionsupporting
confidence: 62%
“…Possible explanations are as follows: rst, the subjects in the study were at different stages of the disease or had different risk factors in addition to the disease; second, previous studies have mostly studied EAT thickness through ultrasound, whereas our study used CMR( as gold standard) to study EAT volume; and third, participants are grouped differently in different studies, which may cause differences in the ndings. Furthermore, the close relationship between BMI and visceral fat has been con rmed, and EAT volume may depend on BMI level [30]. Overall, we highlighted that obesity represented by BMI was the primary risk factor for subclinical left cardiac function impairment in this study, and high EAT levels contribute to risk strati cation for subclinical left cardiac dysfunction.…”
Section: Discussionsupporting
confidence: 62%
“…Possible explanations are as follows: rst, the subjects in the study were at different stages of the disease or had different risk factors in addition to the disease; second, previous studies have mostly studied EAT thickness through ultrasound, whereas our study used CMR( as gold standard) to study EAT volume; and third, participants are grouped differently in different studies, which may cause differences in the ndings. Furthermore, the close relationship between BMI and visceral fat has been con rmed, and EAT volume may depend on BMI level 32 . Overall, we highlighted that obesity represented by BMI was the primary risk factor for subclinical left cardiac function impairment in this study, and high EAT levels contribute to risk strati cation for subclinical left cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 90%
“…Our study showed a strong association between essential AH and EAT in children as young as 12 years old, which raises the question of whether the amount of EAT could be partly genetically predisposed [ 33 ]. The exact pathophysiologic pathway of EAT in cardiovascular disease remains uncertain.…”
Section: Discussionmentioning
confidence: 99%